Comparison of two PET radioligands, [(11)C]FPEB and [(11)C]SP203, for quantification of metabotropic glutamate receptor 5 in human brain - Lohith, Talakad G (J Cereb Blood Flow Metab, 2016)
Of the two (18)F-labeled PET ligands currently available to image metabotropic glutamate receptor 5 (mGluR5), [(18)F]FPEB is reportedly superior because [(18)F]SP203 undergoes glutathionlyation, generating [(18)F]-fluoride ion that accumulates in brain and skull. To allow multiple PET studies on the same day with lower radiation exposure, we prepared [(11)C]FPEB and [(11)C]SP203 from [(11)C]hydrogen cyanide and compared their abilities to accurately quantify mGluR5 in human brain, especially as regards radiometabolite accumulation. Genomic plot was used to estimate the ratio of specific-to-nondisplaceable uptake (BP(ND)) without using a receptor blocking drug. Both tracers quantified mGluR5; however [(11)C]SP203, like [(18)F]SP203, had radiometabolite accumulation in brain, as evidenced by increased distribution volume (V(T)) over the scan period. Absolute V(T) values were ∼30% lower for (11)C-labeled compared with (18)F-labeled radioligands, likely caused by the lower specific activities (and high receptor occupancies) of the (11)C radioligands. The genomic plot indicated ∼60% specific binding in cerebellum, which makes it inappropriate as a reference region. Whole-body scans performed in healthy subjects demonstrated a low radiation burden typical for (11)C-ligands. Thus, the evidence suggests that [(11)C]FPEB is superior to [(11)C]SP203. If prepared in higher specific activity, [(11)C]FPEB would presumably be as effective as [(18)F]FPEB for quantifying mGluR5 in human brain.